Numeros = Numbers. (New York : Sterling Children's Books, 2012)
Photographs of recognizable items invite readers to count from one to ten and backward from ten to one.
On board pages.
Text in English and Spanish.
Keywords: Spanish language materials -- Bilingual; Counting -- Juvenile literature; Contar (Enumerar) -- Literatura juvenil; Board books